Supporting parenting to address social inequalities in health: a synthesis of systematic reviews - Annabelle Pierron; Laurence Fond-Harmant; Anne Laurent; François Alla (BMC, 2018)
Abstract Background In 2009, the World Health Organization's Commission on Social Determinants of Health set out its recommendations for action, which included establishing equity from early childhood onwards by enabling all children and their mothers to benefit from a comprehensive package of quality programmes. In order to address social inequalities in health, it is recommended that action be taken from early childhood, and actions providing support for parenting are an effective lever in this respect. The aim of this review of systematic reviews is to analyse, on the one hand, the components and characteristics of effective interventions in parenting support and, on the other, the extent to which the reviews took into account social inequalities in health. Methods A total of 796 reviews were selected from peer-reviewed journals published between 2009 and 2016 in French or English. Of these, 21 reviews responding to the AMSTAR and selected ROBIS criteria were retained. These were analysed in relation to the consideration they gave to social inequalities in health according to PRISMA-equity. Results The reviews confirmed that parenting support programmes improved infants' sleep, increased mothers' self-esteem and reduced mothers' anger, anxiety and stress levels. The mainly authors noted that the contexts in which the interventions had taken place were described either scantly or not at all, making it difficult to evaluate them. Only half of the reviews had addressed the question of social inequalities in health. In particular, there had been little research conducted on the relational aspect and the social link. Conclusion In terms of addressing social inequalities in perinatal health, the approach remains both modest and reductive. Understanding how, for whom and in what conditions interventions operate is one way of optimising their results. Further research is needed to study the interactions between the interventions and their contexts.